Pandora's vase : a retelling - Meister, Cari.; Kendree, McLean (Mankato, MN : Picture Window Books, 2012)
An illustrated retelling of the Greek myth of Pandora, whose curiosity tempts her to defy Zeus's orders not to open the lid to a beautiful golden vase.
Includes bibliographical references.
Horn Book
Library Media Connection starred
Horn Book, November 2012
Library Media Connection starred, March 2012
3.5
Keywords: Pandora (Greek mythology) -- Juvenile literature; Pandora (Greek mythology); Pandora (Greek mythology)